Effectiveness of physical therapy for locomotive syndrome: A systematic review and meta-analysis protocol - Chadapa Rungruangbaiyok; Hiroyuki Ohtsuka; Charupa Lektip; Jiraphat Nawarat; Eiji Miyake; Keiichiro Aoki; Yasuko Inaba; Yoshinori Kagaya (PLoS ONE, 2025)
Locomotive syndrome, characterized by impaired mobility owing to musculoskeletal disorders, poses a significant public health challenge, especially in aging populations. Locomotive syndrome limits physical activity, increases fall risk, leads to dependency, and diminishes quality of life. Effective interventions are urgently required. This systematic review and meta-analysis aims to evaluate the effectiveness of physical therapy in improving the symptoms of locomotive syndrome. A systematic evaluation of its effectiveness compared with other interventions is crucial for informing clinical practice and policy decisions. This systematic review and meta-analysis will follow the PRISMA-P guidelines. Studies involving individuals diagnosed with locomotive syndrome, without restrictions on age, sex, or location, will be included. The reviewed interventions will include exercise programs, manual therapy, neuromuscular stimulation, and balance training, which will be compared with the absence of interventions or alternative therapies. The primary outcomes will include improvements in functional mobility and physical performance, symptom reduction, and the progression of locomotive syndrome. Secondary outcomes will include adherence to therapy, safety, quality of life, and psychological well-being. Randomized controlled and non-randomized controlled trials published in peer-reviewed journals will be searched in PubMed, CENTRAL, CINAHL, PEDro, Ichushi Web, and the Thai-Journal Citation Index Center, without language restrictions. Independent reviewers will perform data extraction and assess the risk of bias. A meta-analysis will be conducted using RevMan 5.4 software, with subgroup analyses to address heterogeneity. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach will be used to evaluate the certainty of evidence. This review aims to provide robust evidence on the effectiveness of physical therapy in managing locomotive syndrome and to potentially guide clinical practice and healthcare policy decisions.